Prognosis of critical limb ischemia: Major vs. minor amputation comparison. Issue 5 (8th September 2015) - Matsuzaki, Kyoichi; Hayashi, Ruka; Okabe, Keisuke; Aramaki‐Hattori, Noriko; Kishi, Kazuo
ABSTRACT Healthcare providers treating wounds have difficulties assessing the prognosis of patients with critical limb ischemia who had been discharged after complete healing of major amputation wounds. The word "major" in "major amputation" gives the impression of "being more severe" than "minor amputation." Therefore, even if wounds are healed after major amputation, they imagine that prognosis after major amputation would be poorer than that after minor amputation. We investigated the prognosis of diabetic nephropathy patients 2 years after amputations. Those patients underwent dialysis as well as amputation following percutaneous transluminal angioplasty for their foot wounds. They were ambulatory prior to these surgeries. Among 56 cases of minor amputation, 45 were males and 11 were females, and mortality was 41.1%. The mortality of cases with and without a coronary intervention history was 53.1% and 25.0%, respectively (p = 0.034). Among 10 cases of major amputation, 9 were males and 1 was female, and mortality was 60%. The mortality of cases with and without a coronary intervention history was 75.0% and 0%, respectively. Although we predicted poor prognosis in cases with major amputation, there was no significant difference in mortality 2 years after amputations (p = 0.267). Thus far poor prognosis has been reported for major amputation. It might be due to inclusion of the following patients: patients with wounds proximal to ankle joints, patients with extensive gangrene spreading to the lower legs, patients with septicemia from wound infection and who died around the time of operation, and patients with malnutrition. The results of our present study showed that the outcomes at 2 years postoperatively were similar between patients with major amputations and those with minor amputations, if surgical wounds were able to heal. We should not estimate the prognosis by the level of amputation, rather we should consider the effect of coronary intervention history on prognosis.